PEDAL POWERED OPERATED WASHING MACHINE (International Journal of Engineering Sciences & Management Research, 2017)
In many developing countries is impossible to machine wash clothes due to absence or scarcity of electricity or the absence of machine itself. In rural areas there is a lack of electricity. A washing machine is a machine designed to wash laundry, such as clothing, towels and sheets. Generally these machines have been powered by electrical energy but pedal powered machine runs with our energy. The Pedal Operated Washing Machine is the project which is best option for rural area where there is a problem of electric supply or there is shortage of electric supply. In order to overcome and to solve this problem we selected washing machine which operates manually.This does not require any electric power supply or diesel supply.Also, in developed countries these pedal operated machine can be used to save electricity and doing some work out.This project is low in weight and portable so that it can be easily transported.we use the simple cycling mechanism to run the machine shaft.In this project fabrication and analysis of pedal based washing machine is done, performance parameters are calculated on the basis of load and weight.